Modelling paralytic shellfish toxins (PST) accumulation in Crassostrea gigas by using Dynamic Energy Budgets (DEB) - Pousse, Emilien; Flye-Sainte-Marie, Jonathan; Alunno-Bruscia, Marianne; Hegaret, Helene; Rannou, Eric; Pecquerie, Laure; Marques, Gonçalo, M.; Thomas, Yoann; Castrec, Justine; Fabioux, Caroline; Long, Marc; Lassudrie, Malwenn; et al. (Journal of Sea Research, 2019)
International audience As other filter-feeders, Crassostrea gigas can concentrate paralytic shellfish toxins (PST) by consuming dino-flagellate phytoplankton species like Alexandrium minutum. Intake of PST in oyster tissues mainly results from feeding processes, i.e. clearance rate, pre-ingestive sorting and ingestion that are directly influenced by environmental conditions (trophic sources, temperature). This study aimed to develop a mechanistic model coupling the kinetics of PST accumulation and bioenergetics in C. gigas based on Dynamic Energy Budget (DEB) theory. For the first time, the Synthesizing Units (SU) concept was applied to formalize the feeding preference of oysters between non-toxic and toxic microalgae. Toxin intake and accumulation were both dependent on the physiological status of oysters. The accumulation was modelled through the dynamics of two toxin compartments: (1) a compartment of ingested but non-assimilated toxins, with labile toxins within the digestive gland eliminated via faeces production; (2) a compartment of assimilated toxins with a rapid detoxification rate (within a few days). Firstly, the DEB-PST model was calibrated using data from two laboratory experiments where oysters have been exposed to A. minutum. Secondly, it was validated using data from another laboratory experiment and from three field surveys carried out in the Bay of Brest (France) from 2012 to 2014. To account for the variability in PST content of A. minutum cells, the saxitoxin (STX) amount per energy units in a toxic algae (ppsT) was adjusted for each dataset. Additionally, the effects of PST on the oyster bioenergetics were calibrated during the first laboratory experiment. However, these effects were shown to depend on the strain of A. minutum. Results of this study could be of great importance for monitoring agencies and decision makers to identify risky conditions (e.g. production areas, seawater temperature), to properly assess detoxification step (e.g. duration, modalities) before any commercialization ...